Comparison of carbon storage and oxygen release in various land uses in North Luwu District, South Sulawesi Province, Indonesia - DICKY DICKY; SAMUEL A. PAEMBONAN; MUKRIMIN MUKRIMIN; SYAMSUDDIN MILLANG; WITNO WITNO; AHMAD RIFQI MAKKASAU; BUDI ARTY; WISNU RAMADHAN; AMAL RASYID (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Dicky D, Paembonan SA, Mukrimin M, Millang S, Witno W, Makkasau AR, Arty B, Ramadhan W, Rasyid A. 2025. Comparison of carbon storage and oxygen release in various land uses in North Luwu District, South Sulawesi Province, Indonesia. Biodiversitas 26: 2754-2761. The ability of plants to absorb CO? from the atmosphere and store carbon in their biomass determines the success of climate change mitigation programs. This study compared the carbon storage capacity, CO? absorption, and oxygen release in three types of land use in North Luwu District, South Sulawesi Province, Indonesia, namely secondary natural forest, cocoa agroforestry, and oil palm plantation. The study was conducted in two stages: field activities to collect vegetation data and laboratory analysis conducted at the Faculty of Forestry, Universitas Hasanuddin, South Sulawesi. Tree biomass was estimated using allometric equations based on tree diameter and height, while understory and litter biomass were calculated using the dry weight and carbon content methods. The results show significant differences in carbon storage capacity among land uses. Secondary natural forest has the highest carbon storage capacity (264.45 tC ha-1), which contributes to the absorption of 969.65 tCO2 ha-1 and the release of 705.2 tO2 ha-1. High biodiversity and complex vegetation structures allow natural secondary forests to absorb more carbon through photosynthesis. Cocoa agroforestry has a carbon storage capacity of 182.43 tC ha-1, absorption of 668.90 tCO2 ha-1, and release of 486.48 tO2 ha-1. This difference is due to the simpler vegetation structure of cocoa agroforestry compared to natural secondary forest. Meanwhile, oil palm plantation has the lowest carbon storage capacity (123.92 tC ha-1), absorption of 454.38 tCO2 ha-1, and release of 330.46 tO2 ha-1. Our findings suggest that cocoa agroforestry is still superior to oil palm plantation because the presence of shade trees and cultivated plants, and monoculture system is less effective in mitigating climate change.